Заповідна справа : навчально-методичний комплекс з дисципліни - Максименко, Надія Василівна; Maksimenko, Nadiya V. (Харків : Харківський національний університет імені В.Н. Каразіна, 2022)
Навчальна дисципліна «Заповідна справа» належить до нормативних дисциплін підготовки еколога, що зумовлює необхідність засвоєння студентами базових знань у галузі природно-заповідної справи, які забезпечать успішну подальшу роботу за обраною спеціальністю. Курс «Заповідна справа» знайомить з теоретичними основами природно-заповідної справи, основними етапами розвитку природно-заповідної справи в Україні, мотивацією створення об’єктів природно-заповідного фонду, їх структурою, проблемами і перспективами функціонування, а також особливостями природи у природних і біосферних заповідниках, національних природних парках України і світу. Навчальне видання призначене для організації роботи студентів у закладах вищої освіти за спеціальністю 101 «Екологія» першого (бакалаврського) освітнього рівня.

The educational discipline "Reserved business" belongs to the regulatory disciplines of training an ecologist, which necessitates the acquisition by students of basic knowledge in the field of nature-reserved business, which will ensure successful further work in the chosen specialty. The course "Conservation Affairs" introduces the theoretical foundations of nature conservation affairs, the main stages of the development of nature conservation affairs in Ukraine, the motivation for the creation of objects of the nature conservation fund, their structure, problems and perspectives of functioning, as well as the peculiarities of nature in natural and biosphere reserves, national natural parks of Ukraine and the world. The educational edition is intended for organizing the work of students in institutions of higher education on the specialty 101 "Ecology" of the first (bachelor's) educational level.
Protected business: educational and methodological complex of the discipline
Keywords: FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; заповідна справа; поліфункціональність природно-заповідних територій; міжнародна класифікація; регіональні особливості організації природно-заповідних територій; міжнародні природоохоронні конвенції; міжнародні природоохоронні угоди; «червоні» переліки видів; природно-заповідна справа в Україні; поліфункціональність природно-заповідних територій; структура природно-заповідного фонду України; організаційно-правові засади ведення природно-заповідної справи; екологічна мережа України; наукові дослідження на природно-заповідних територіях; програма «Літопис природи»; структура природно-заповідного фонду України; зонально-регіональні особливості природно-заповідного фонду України; методи контролю; система оцінювання; відео-лекції; питання для самоперевірки; практичні роботи; самостійна робота; приклади завдань семестрових екзаменів; protected matter; examples of semester exam tasks; independent work; practical works; self-test questions; video lectures; information resources on the Interne; multi-functionality of nature-protected areas; evaluation system; control methods; zonal and regional features of the nature reserve fund of Ukraine; "Chronicle of Nature" program the structure of the Nature Reserve Fund of Ukraine; scientific research in nature reserves; international classification; ecological network of Ukraine; organizational and legal principles of management of nature reserve affairs; multi-functionality of nature-protected areas the structure of the Nature Reserve Fund of Ukraine; nature reserve case in Ukraine; "red" lists of species; international environmental agreements; international environmental conventions; regional features of the organization of nature reserves